NATURE-INSPIRED LEADERSHIP — SEEKING HUMAN-TECHNOLOGY-EARTH HARMONY - Botha, Anthon (The South African Journal of Industrial Engineering, 2020)
“Go to the ant, … consider its ways and be wise!” (Proverbs 6:6). We have progressed using biomimicry to inform our engineering designs and processes. Yet we have learnt very little in finding our inspiration from nature for leading in our complex world. In nature, those species that learn by observing, listening, making sense, internalising, thinking, and resting at the right time, survive and thrive in their environments — on plains, in mountains, in the bush, rivers, oceans, deserts, and the sky. Fight or flight takes place in both nature and business. Challenges are shared in co-existence, patience, perseverance, resilience, and adaptation. Leadership challenges that are emerging in the new world of human and machine co-existence will also be enriched by lessons from nature that inspire new behaviour, that are not conceived in business schools or legacy cultures, but that are flexible, effective, and work efficiently — as natural solutions have done for millennia. We discuss the makings of a conceptual thought model of leadership inspired by nature. It is a starting point to create an awareness of how nature-inspired leadership may be applied. Yet, when modelling anything on nature, one has to realise that all models are simplifications, which means that nature itself, as a complex system, is not fully understood. Our aim should not be to copy nature, but to extract principles from it.